If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2h+3h=14
We move all terms to the left:
-2h+3h-(14)=0
We add all the numbers together, and all the variables
h-14=0
We move all terms containing h to the left, all other terms to the right
h=14
| 5/7m−1/7=7/42 | | f(2)=2/2 | | 7-(4+3t)+2t=6(t-2)-5 | | 3x+3x-2=16 | | (2x+10)+(2x+2)=180 | | 11+3-x=10+3-2x | | 25x+100=125 | | 21=14=17+7x | | -3(2p-7)+4p=15 | | 3j=14.46 | | 7+7(2x+7)=7(1+3x) | | -2x+21=-6x+3+6 | | 12x+1+13x+4=180 | | 5t+16=6-5t. | | f+3=6.57 | | 4(b-19)=-4 | | 2c+10c=-12 | | -1=y/3-2 | | (6x+22)(7x+16)=90 | | -9k+k=16 | | 7-14m=2m+-5 | | 65=-4(n-1) | | 8g=-24 | | 12m+27=3(4m+9) | | x^2=25/676 | | -4.3=w/4+2.1 | | 8(-4=7x)-4(5x-7)=72 | | 2x+20=1/2(x+50) | | 7x+6=-8+5x | | -499+8=9(6r-7) | | 7+7(2x+7)=71+3x)7+7(2x+7)=7(1+3x) | | 6=2(v-3) |